Teacher Experiences of Using Kahoot to Support Inclusive Classrooms in English Language Learning: Teacher Practice and Experiences - Devi Adelia; Utami Dewi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines the teacher experiences in using Kahoot in inclusive classrooms for English language learning. The methodology applied is a qualitative case study approach. The research participants consisted of four English teachers from an inclusive elementary school in North Sumatra, who were selected through purposive sampling. Data collection instruments: a 15-item questionnaire (5-point Likert scale) and semi-structured interviews. Data analysis was conducted using thematic analysis to identify themes from the teacher experiences. The findings show that Kahoot creates a fun learning environment and increases student engagement, especially for those with special needs. Approximately 75% of teachers believed that Kahoot increased student engagement and created an interactive learning experience. Although teachers felt capable of managing the class, challenges in classroom management remained, emphasizing the importance of communication and preparation. The implications of this study indicate the need for schools to provide training and support so that teachers can effectively integrate this technology into their teaching.